Controlling particle size in a novel spinning disc continuous stir tank and settler reactor for the continuous synthesis of titania - Akindeju, Michael; Ong, P. (Elsevier B V, 2011)
In this study, we present a Novel Spinning Disc Continuous Stir Tank and Settler Reactor which has the ability to produce nanoparticles with specified morphology, particle size and distribution. This control is achieved by combining a Rotating Disc and a Continuous Stir Tank Reactor. The reactor control has been modelled using a simplified model (Ronald’s equation), parameters of which (such as Young’s modulus) were calculated using molecular modelling. The model was then used to study the effect of TiCl4/H2O molar ratio, TiCl4 concentration, spinning disc and CSTR impeller rotation speeds. We have in this work defined a Viscosity Power Correction Factor (VPCF) which correlates the characteristic shear and Young’s moduli, for each polymorph, with actual operating conditions to achieve parameterised key indicators to obtain the critical breaking stress for desired critical particle radii; and hence obtained an adequate control for particle size and distribution when coupled with the degree of super-saturation.